Trump-Era Visa Policies and the Transformation of US Education Diplomacy: Implications for Islamic Education and Global Geopolitics - Arofah Minasari; Dewi Wardah Mazidatur Rohmah; Afrizal Fajri (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the impact of President Donald Trump’s visa policies on shifts in US education diplomacy within the context of global geopolitics, with particular attention to their implications for international students from Muslim-majority countries and Islamic education networks. Restrictive measures during his administration, including limitations on F-1 and J-1 visas and travel bans targeting several Muslim-majority states, led to a notable decline in international student mobility and weakened the United States’ position as a leading global education destination. Using a descriptive qualitative approach and desk study method, this research is supported by individual-level foreign policy theory and education diplomacy theory. The analysis explores how Trump’s perceptions and leadership style shaped policies affecting higher education, including Islamic education-oriented exchanges and collaborations. It also highlights responses from competing countries such as Canada, Australia, and China, which expanded inclusive education policies and strengthened engagement with Islamic and Global South students. The findings show that these visa policies reduced US soft power and created opportunities for other states to lead in global education diplomacy, underscoring the need for more inclusive policy reforms.